Paritas, Age, and Education Are Associated with the Level of Anxiety in Facing the Childbirth Period in PMB Komang Seni Rahayu, A.Md.Keb - Fitriana Suandari, Kadek Indah; Tangkas, Made; Adhiestiani, Ni Made E gar (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2023)
Pregnancy-related anxiety is a condition that arises from the subjective experience of unsettling mental tension as a general reaction and the inability to deal with issues or feelings of insecurity that affect pregnant women and are related to the mother's concern for the welfare of herself and her fetus. The pregnant woman's age, education level, and prior pregnancies and deliveries are risk factors that contribute to anxiety in pregnant women. Particularly throughout the third trimester of pregnancy up until delivery, anxiety can strike pregnant women. Pregnant women experience anxiety during this time, including worry about having a healthy baby or worrying about the discomfort they are experiencing. These diseases can raise the risk of bleeding wounds and uterine atony, while also raising the likelihood of preterm birth and low birth weight in babies. This study's main goal was to find out how third-trimester pregnant women at PMB Komang Seni Rahayu, A.Md.Keb related to parity, age, and education. This study is quantitative and cross-sectional in nature. A questionnaire that was distributed to a specified group of respondents was used to collect data using the purposive sampling technique. 32 samples total were used in this study. Both univariate and bivariate data analysis are used in this study. Results of the correlations statistical test (= 0.05). The findings revealed a correlation between parity, age, and education with the degree of anxiety associated with giving birth in third-trimester pregnant women at PMB Komang Seni Rahayu, A.Md.Keb, with a significance of p = 0.139 at parity, age with p = 0.005, and level of education with 0.628. Keywords : Characteristics, Pregnant Women, Anxiety